2010
DOI: 10.3109/01480540903431457
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the percutaneous penetration and distribution of uranyl nitrate as a function of skin-barrier integrity: anin vitroassessment

Abstract: As recommended by OECD Guidelines, percutaneous penetration studies consider intact skin, but rarely injured skin. Recent years have witnessed a growing concern for these two types of dermal exposure in the industry, particularly in the nuclear industry. The aim of this study was to show that a method based on an in vitro device can be used to realistically assess how skin-barrier alterations caused by occupational accidents can modify the percutaneous penetration and distribution of radionuclides, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Petitot et al . () studied percutaneous penetration of uranyl nirate through chemically burned rat skin. They found no significant difference in uranium concentration between 10 n NaOH burned skin and intact skin.…”
Section: Chemical Irritationmentioning
confidence: 97%
See 1 more Smart Citation
“…Petitot et al . () studied percutaneous penetration of uranyl nirate through chemically burned rat skin. They found no significant difference in uranium concentration between 10 n NaOH burned skin and intact skin.…”
Section: Chemical Irritationmentioning
confidence: 97%
“…They presumed the effect was due to a conformational collapse of the protein in this layer and a consequent increase in porosity from the damaged ductal epithelium of the exocrine glands. Petitot et al (2007Petitot et al ( , 2010 studied percutaneous penetration of uranyl nirate through chemically burned rat skin. They found no significant difference in uranium concentration between 10 N NaOH burned skin and intact skin.…”
Section: Chemical Irritationmentioning
confidence: 99%
“…In spite of the lack of attention paid to skin as a route or target organ for uranium exposure in epidemiological studies, the dermal uptake of uranium is well established. Animal studies have shown that uranium passes through both intact and injured skin to reach other target organs (de Rey et al, 1983;López et al, 2000;Petitot et al, 2010;Spagnul et al, 2011). Monitoring of Gulf War veterans with uranium-containing shrapnel embedded in their skin has determined that the shrapnel dissolves and the uranium migrates to systemic organs and is excreted in urine (Leggett and Pellmar, 2003;McDiarmid et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Other uranium compounds (uranium tetrachloride or tetrafluoride, uranium trioxide) are absorbed through the skin of mice, rats, and guinea pigs at a rate of 0.1% of dermally applied uranium, a relatively low absorption rate (Orcutt, 1949). Also other studies show that soluble uranium compounds can be absorbed through the skin (Petitot et al, 2007(Petitot et al, , 2010, however, the concentrations of uranium applied to the skin were extremely high, and it is unlikely that humans would typically experience such exposures.…”
Section: Dermalmentioning
confidence: 99%